China-Kazakhstan: cooperation and innovation in education as part of the belt and road initiative - А.Б., Дуйсекина; Ж.Е., Ашинова (Journal of Oriental Studies, 2020)
The dynamic economic growth of China, the expansion of trade, the huge demographic potential, the development of innovations and the introduction of new technologies have attracted the attention of politicians and researchers from around the world. A new level of economic integration between Kazakhstan and China requires enhanced cooperation not only in the political, trade, financial sectors, but also, which is no less important, in the field of education and innovation. This is because not only politicians, businessmen, but also ordinary people will join the system of relations in the process of the economic integration of the two countries, with their help joint production and joint products will be created. Implementation of the Belt and Road initiative raises new challenges for Kazakhstan and China’s cultural and educational spheres. The goal of the research is to examine the prospects of cooperation and innovation in the field of education within the context of the Belt and Road initiative, identify the main areas of educational cooperation and identify key areas of cooperation between Kazakhstan and China. This article contributes to the sense of the Belt and Road initiative to improve the theory and practice of international cooperation between China and Kazakhstan in the field of education and innovation. Key words: cooperation, education, Belt and Road initiative, Kazakhstan, China.